Unraveling the complexity of IgG4-related aortitis and periarteritis: from pathogenesis to clinical practice - Wang, Yan; Tian, Feng; Li, Hui (Frontiers in Immunology, 2025)
IgG4-related disease (IgG4-RD) is a chronic fibrotic inflammatory condition characterized by elevated serum IgG4 levels and the infiltration of IgG4-bearing plasma cells in affected organs. It can involve various organs, particularly large vessels. IgG4-related aortitis/periaortitis and periarteritis (IgG4-related PAO/PA) predominantly affect the abdominal aorta and iliac arteries, with a higher prevalence in elderly males. This condition exhibits distinct clinical, histologic, and radiological features compared to IgG4-RD without vascular involvement and other immune-associated vasculitides. IgG4-related PAO/PA diagnosis primarily relies on histopathological findings and imaging studies. Glucocorticoids (GCs) are the mainstay of treatment, often combined with immunosuppressants (IMs), while B- and T-cell-targeted therapies are under investigation. Although most patients respond well to treatment, the disease can be life-threatening due to complications such as myocardial infarction, aortic dissection, and aneurysmal rupture. Therefore, understanding these characteristics is crucial for clinicians to make accurate diagnoses and implement effective treatment strategies. This review provides a comprehensive overview of the current understanding of the pathogenesis, histopathological characteristics, clinical features, diagnosis, treatment, and prognosis of IgG4-related PAO/PA.